Disease Management, Coping, and Functional Disability in Pediatric Sickle Cell Disease - Oliver-Carpenter, Gloria (J Natl Med Assoc, 2011)
BACKGROUND: Youth with sickle cell disease (SCD) experience chronic symptoms that significantly interfere with physical, academic, and social-emotional functioning. Thus, to effectively manage SCD, youth and caregivers must work collaboratively to ensure optimal functioning. The goal of the current study was to examine the level of involvement in disease management tasks for youth with SCD and their caregivers. The study also examined the relationship between involvement in disease management tasks, daily functioning, and coping skills. The study utilized collaborative care and disease management theoretical frameworks. METHODS: Youth and caregivers participated in the study during an annual research and education day event. Forty-seven patients with SCD aged 6 to 18 years and their caregivers completed questionnaires examining level of involvement in disease management tasks, youth functional disability and youth coping strategies. Caregivers also completed a demographic and medical history form. RESULTS: Parents and youth agreed that parents are significantly more involved in disease management tasks than youth, although level of involvement varied by task. Decreased parent involvement was related to greater coping strategies used by patients, including massage, prayer, and positive thinking. Higher functional disability (lower functioning) was related to greater parent involvement in disease management tasks, suggesting that greater impairment may encourage increased parent involvement. CONCLUSIONS: Health professionals working with families of youth with SCD should discuss with parents and youth how disease management tasks and roles will be shared and transferred during adolescence. Parents and youth may also benefit from a discussion of these issues within their own families.